Motivasi dan Persepsi Mahasiswa dalam Memilih Program Studi Komunikasi dan Penyiaran Islam IAI Muhammadiyah Sinjai - Faridah (LP2M IAI Muhammadiyah Sinjai, 2020)
This study aims to explore students' motivation and perceptions in choosing the IAIM Sinjai Islamic communication and broadcasting study program (KPI) and to analyze the opportunities for developing the KPI Study Program. The method that researchers use is exploratory with a qualitative approach. The research subjects were 27 KPI IAIM Sinjai students out of 54 active students with the object of research being students' motivation and perceptions in choosing study programs. From the results of the study, it was explained that students chose the KPI study program because they were motivated to strengthen and develop their communication skills and the desire to pursue several professions, namely becoming practitioners and academics of da'wah and communication. As for the perception of KPI students related to the study program they have chosen, it is a study program whose alumni are needed by public and private agencies and are in great demand but not yet widely known among the public, especially in Sinjai so that the opportunities for developing study programs are very large by conducting a lot of socialization, strengthening the competence of graduates and increase the value of accreditation.